PENGEMBANGAN HANDOUT ELEKTRONIK BERBASIS ETNOSAINS PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Zurhidayati Zurhidayati; Yuslim Fauziah; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to produce an Ethnoscience-Based Electronic Handout on Biodiversity Materials for Class X SMA. The research was carried out at the Biology Education Study Program, FKIP UNRI and at SMA Negeri 2 Pekanbaru for students at SMA Negeri 2 Pekanbaru from August to December 2021. This type of research used the ADDIE model. The instruments used are validation sheets and response questionnaires. The results showed that the well-developed electronic handouts were appropriate to be used as additional teaching materials in the learning process in schools to increase students' knowledge and understanding of biodiversity materials in facilitating students to build their own knowledge. The results of the validation of the Ethnoscience-Based Electronic Handout on Biodiversity Materials for Class X SMA shows that the electronic Handout that has been developed is in the very valid category with an overall average score of 3.51. The results of the first stage of the trial obtained an average score of 3.37 and the results of the second stage of the trial obtained an average score of 3.38 in the very good category.Key Words:Electronic Handout, Ethnoscience, Biodiversity.